1982
DOI: 10.1093/oxfordjournals.jhered.a109622
|View full text |Cite
|
Sign up to set email alerts
|

2,4-D induced clastogenicity and elevated rates of sister chromatid exchanges in cultured human lymphocytes

Abstract: Potential for genetic damage in future generations from such widely used hormonic herbicide as 2,4-D (2,4-dichlorophenoxyacetic acid) is of serious concern. Yet the data, particularly on mammalian systems, continue to be inadequate and inconclusive. An attempt was made in this study to determine the clastogenic and mutagenic potential of 2,4-D in cultured lymphocytes. Chromosome damage though statistically insignificant occurred at dosages as low as 0.2 microgram/ml. Chromosome damage was increased at a statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 0 publications
2
9
0
1
Order By: Relevance
“…The authors suggested that perhaps some unidentified clastogenic agents, such as chlorophenol contaminants, are responsible for the increases detected. This suggestion would perhaps explain the positive results obtained previously [Korte and Jalal, 1982] where no indication about the purity of the compound used was reported and, at the same time, would agree with the work by Högstedt et al [Högstedt Frei and Würgler (1988); +, positive; -, negative; i, inconclusive; m = multiplication factor; probability levels: α = β = 0.05. et al, 1980], who did not find chromosome aberration increases in the lymphocytes of Swedish herbicide sprayers exposed to these chemicals.…”
Section: Resultssupporting
confidence: 88%
“…The authors suggested that perhaps some unidentified clastogenic agents, such as chlorophenol contaminants, are responsible for the increases detected. This suggestion would perhaps explain the positive results obtained previously [Korte and Jalal, 1982] where no indication about the purity of the compound used was reported and, at the same time, would agree with the work by Högstedt et al [Högstedt Frei and Würgler (1988); +, positive; -, negative; i, inconclusive; m = multiplication factor; probability levels: α = β = 0.05. et al, 1980], who did not find chromosome aberration increases in the lymphocytes of Swedish herbicide sprayers exposed to these chemicals.…”
Section: Resultssupporting
confidence: 88%
“…Similarly to our findings, Korte and Jalal (1982) reported that 2,4-D had induced chromosomal aberrations in human PBLs in vitro with concentrations of 50 and 60 lg/mL. Madrigal-Bujaidar (2001) observed that 2,4-D had a moderate genotoxic effect in mice that were treated in vivo with high concentrations (100 and 200 mg/kg) of this compound.…”
Section: Discussionsupporting
confidence: 90%
“…Korte and Jalal [191] evaluated the clastogenic and mutagenic potential of 2,4-D in cultured lymphocytes. Chromosomal damage, though statistically insignificant, occurred at doses as low as 0.2  μ g/mL and increased at a statistically significant level at concentrations of 50  μ g/mL or higher.…”
Section: Toxicological Studiesmentioning
confidence: 99%